Cannabinoid receptors are localized to noradrenergic axon terminals in the rat frontal cortex - Oropeza, Veronica C. (2006)
Cannabinoid agonists exert complex actions on modulatory neurotransmitters involved in attention and cognition. Previous studies have demonstrated that acute systemic administration of the synthetic cannabinoid agonist, WIN 55,212-2, increases norepinephrine efflux in the rat frontal cortex. In an effort to elucidate whether cannabinoid (CB1) receptors are positioned to presynaptically modulate norepinephrine release in the frontal cortex, immunocytochemical detection of the CB1 receptor and the catecholamine-synthesizing enzyme dopamine-β-hydroxylase (DβH) was performed using confocal immunofluorescence microscopy and immunoelectron microscopy in rat brain. Fluorescence microscopy analysis of dually-labeled tissue sections from the frontal cortex indicated that individual axonal processes exhibited both CB1 receptor and DßH immunoreactivities. Ultrastructural analysis confirmed that one-third of axon terminals containing CB1 immunolabeling also exhibited DβH labeling. Cortical neurons were also found to be targeted by separately labeled CB1- and DβH-containing axon terminals. In conclusion, the present neuroanatomical data suggest that cortical norepinephrine release may be modulated, in part, by CB1 receptors that are presynaptically distributed on noradrenergic axon terminals.